Piezoelectric microphone via a digital light processing 3D printing process. (5th March 2019) - Tiller, Benjamin; Reid, Andrew; Zhu, Botong; Guerreiro, José; Domingo-Roca, Roger; Curt Jackson, Joseph; Windmill, J.F.C.
Abstract: In nature sensors possess complex interlocking 3D structures and extremely localized material properties that allow processing of incredibly complex information in a small space. Acoustic sensor design is limited by fabrication processes, often MEMS based, where there is limited scope for fully 3D creations due to planer fabrication methods. Here we investigate the application of 3D printing via digital light processing (DLP) to integrate piezoelectric, conductive and structural polymer layers to create a complete electro-mechanical device. We demonstrate a working piezoelectric acoustic sensor, capable of sending electric signals that can be picked up by pre-amp circuitry fabricated using a commercially available 3D printer. We show that the 3D printing of mechanically sensitive membranes with thicknesses down to 35 μm and tunable resonant frequencies is possible and further show it is possible to create a fully working electro-acoustic device by embedding 3D printed piezoelectric and conductive parts. Realizing this design opens up the possibility of generating truly 3D structured functional prints that may be used in bio-inspired design. Graphical Abstract: Highlights: Demonstration of fully 3D printed working piezoelectric microphone. Characterization of resin properties and print results for Barium Ti- tanate nanoparticles and Multi-Walled Carbon Nanotube in a polymer matrix. Adaptation of commercial digital light processing 3D printer to multi- material integrated build.